Globalizácia v strategickom kontexte vnemy a očakávania podnikov - Javor, Miroslav (2007)
Fundamental idea of presented doctoral dissertation is that investigating deeper implications of globalisation requires a specific contextual approach based on combination of interdisciplinarity and non-analytical methods, both in general and in terms of business strategy. Red line of the thesis is effort to narrow down the globalisation concept to empirically testable form on business level without loosing grip of the unique essence of this social phenomenon. The result of my research in given direction is introduction of an alternative way to expand objective understanding of globalisation on business level. This is accomplished by the means of explaining the relation between globalisation-related perceptions and expectations of business and by further utilization of this objective characteristic of contemporary globalisation for testing the relevance of other related relations within business strategy